2019
DOI: 10.1111/bjop.12380
|View full text |Cite
|
Sign up to set email alerts
|

Flexible representations in visual working memory and interactions with long‐term learning: Commentary on the special issue

Abstract: This special issue of the British Journal of Psychology brings together cutting edge research on a range of topics in visual working memory (VWM). In this commentary, we attempt to summarize common themes in current VWM research exemplified in this issue. The articles include several reviews of important topics as well as empirical papers covering three main themes. The first concerns the nature of mental representations of memoranda in the commonly used delayed estimation task, where both fine-grained and bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…The role of long-term memory in WM ( Jensen and Lisman, 2005 ) remains controversial. The observation of prefrontal-hippocampal synchrony during WM maintenance ( Brincat and Miller, 2015 ) seems consistent with the suggestion that the hippocampus supports WM by activating long-term memory representations ( Eriksson et al, 2015 ; Loaiza and Halse, 2019 ; Rhodes and Cowan, 2019 ). In support of recruitment of the hippocampus during WM, there is evidence for an increase in the γ band power within PFC and the hippocampus during WM ( Brzezicka et al, 2019 ), and imaging studies have shown an interaction between PFC and the hippocampus during WM tasks ( Gluth et al, 2015 ; Calabro et al, 2020 ).…”
Section: Synchronization Between Areas During Working Memory Predicts Performancesupporting
confidence: 86%
See 1 more Smart Citation
“…The role of long-term memory in WM ( Jensen and Lisman, 2005 ) remains controversial. The observation of prefrontal-hippocampal synchrony during WM maintenance ( Brincat and Miller, 2015 ) seems consistent with the suggestion that the hippocampus supports WM by activating long-term memory representations ( Eriksson et al, 2015 ; Loaiza and Halse, 2019 ; Rhodes and Cowan, 2019 ). In support of recruitment of the hippocampus during WM, there is evidence for an increase in the γ band power within PFC and the hippocampus during WM ( Brzezicka et al, 2019 ), and imaging studies have shown an interaction between PFC and the hippocampus during WM tasks ( Gluth et al, 2015 ; Calabro et al, 2020 ).…”
Section: Synchronization Between Areas During Working Memory Predicts Performancesupporting
confidence: 86%
“…Distributed network models of WM posit that interactions between association areas (such as parietal and prefrontal cortex) are necessary for memory maintenance ( Leavitt et al, 2017 ). In the activation of long-term memory theory, PFC-hippocampal interactions maintain WM via activation of long-term memory representations ( Eriksson et al, 2015 ; Loaiza and Halse, 2019 ; Rhodes and Cowan, 2019 ); it has also been suggested that information must pass through WM before entering long-term memory ( Eriksson et al, 2015 ; Loaiza and Halse, 2019 ; Rhodes and Cowan, 2019 ). Synchrony between the PFC and areas associated with long-term memory (such as the hippocampus) could reflect either of these processes.…”
Section: Synchronization Between Areas During Working Memory Predicts Performancementioning
confidence: 99%
“…The collection of articles is rounded off by an integrative commentary by Rhodes and Cowan (). Although some current topics, such as the active manipulation of VWM content (e.g., Christophel, Cichy, Hebart, & Haynes, ; Liesefeld & Zimmer, ) and the relationship of LTM and VWM (e.g., Brady, Störmer, & Alvarez, ; Schurgin, Cunningham, Egeth, & Brady, ) are underrepresented here, we believe that reading through the articles in this issue provides a relatively comprehensive overview on the current state of VWM research.…”
mentioning
confidence: 99%